Hemoglobin induces inflammation through NF-kB signaling pathway and causes cell oxidative damage in grass carp (Ctenopharyngodon idella) - Tang, Ying; Yang, Shiyi; Yao, Minshan; Yang, Minxuan; Wei, Lixiang; Chen, Hong; Lin, Junyan; Huang, Yao; Lin, Li; Qin, Zhendong (Frontiers in Immunology, 2022)
Hemolytic disease in grass carp (C. idella) leads to hemolysis in vivo, releasing damage-related molecular patterns (DAMPs) hemoglobin (Hb; which is rapidly oxidized to Hb-Fe3+ and Hb-Fe4+) and generating a high level of reactive oxygen species (ROS) that cause oxidative damage. However, the effect of cell-free Hb on tissue cells of grass carp has yet to be elucidated. In this study, a grass carp hemolysis model was constructed by injection of phenylhydrazine (PHZ). Western blotting (WB) and immunofluorescence analysis (IFA) showed that PHZ-induced hemolysis caused Hb and iron accumulation, and ROS production and apoptosis were confirmed to be significantly increased in the head kidney and middle kidney of the grass carp following PHZ administration. Quantitative real-time PCR (qRT-PCR), WB, and IFA revealed that PHZ-induced hemolysis could upregulate the expression of inflammation-related genes through activation of the NF-κB signaling pathway. To further explore the effect of Hb, three forms of Hb (Hb, MetHb, and FerrylHb) were prepared. Expression of cytokine genes was markedly upregulated after incubation with the different forms of Hb and heme, and this was further confirmed to occur through activation of the NF-κB signaling pathway. Flow cytometry analysis data of ROS and apoptosis showed that the stimulation of different forms of Hb and heme increased the production of ROS, and resulted in apoptosis. In summary, data from this study suggest that the excess cell-free Hb released during hemolysis modulates the inflammatory response though activation of the NF-κB signaling pathway and causes oxidative damage and apoptosis.